2016
DOI: 10.17973/mmsj.2016_10_201695
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Modified Pinewood on the Quality of Machining at Plain Milling

Abstract: The theory and practice in engineering industry is not the same. Durability of cutting tools is defined in standard ISO 3685. In standard ISO 3685 is defined T-vc dependence for different cutting materials and standard included process evaluation of tool durability for cutting materials made of high speed steel, sintered carbide and cutting ceramic. Standard ISO 3685 contains instructions how to create T-vc dependence for cutting tools made of cutting ceramic. In this standard are only instructions how to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Thus, with an increase in feed speed surface roughness will increase. This dependence has been confirmed by many authors both for solid wood (Kvietková et al 2015;Vanco et al 2016) and for wood-based materials (Davim et al 2009;Guo et al 2015). For cutting power, an increase in this parameter was observed with an increase in chip thickness and cutting speed.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Thus, with an increase in feed speed surface roughness will increase. This dependence has been confirmed by many authors both for solid wood (Kvietková et al 2015;Vanco et al 2016) and for wood-based materials (Davim et al 2009;Guo et al 2015). For cutting power, an increase in this parameter was observed with an increase in chip thickness and cutting speed.…”
Section: Resultssupporting
confidence: 73%
“…Another study by Aguilera and Martin (2001) tested beech wood while applying three cutting speeds and observed comparable roughness for all the conducted tests. Some reports have also been published where researchers stated an effect of cutting speed on surface roughness (Kvietková et al 2015), whereas other authors confirmed this dependence only in some cases (Ispas et al 2016;Vanco et al 2016) or reported only a slight effect (Han et al 2004). In turn, cutting speed significantly affects cutting power.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations